2014
DOI: 10.1063/1.4901124
|View full text |Cite
|
Sign up to set email alerts
|

A hydrogel capsule as gate dielectric in flexible organic field-effect transistors

Abstract: A jellified alginate based capsule serves as biocompatible and biodegradable electrolyte\ud system to gate an organic field-effect transistor fabricated on a flexible substrate.\ud Such a system allows operating thiophene based polymer transistors below\ud 0.5 V through an electrical double layer formed across an ion-permeable polymeric\ud electrolyte. Moreover, biological macro-molecules such as glucose-oxidase\ud and streptavidin can enter into the gating capsules that serve also as delivery system.\ud An en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Edible electrolytic matrixes of chitosan, cellulose, agarose, and gelatin with dispersed salts have been also exploited within transistor architectures. [ 121,122,132,133 ] It is also important to acknowledge the relevance of electrolytes in electrochromic technologies. [ 134 ]…”
Section: Edible Materials: Ingredients For a Future Edible Electronicmentioning
confidence: 99%
“…Edible electrolytic matrixes of chitosan, cellulose, agarose, and gelatin with dispersed salts have been also exploited within transistor architectures. [ 121,122,132,133 ] It is also important to acknowledge the relevance of electrolytes in electrochromic technologies. [ 134 ]…”
Section: Edible Materials: Ingredients For a Future Edible Electronicmentioning
confidence: 99%
“…They showed that, in dry state, BSA-gated pentacene OFETs exhibited a threshold voltage of ca.ÂŽ16 V, whereas the V TH was reduced toÂŽ0.7 V under humid conditions. Very recently, Dumitru et al [107] used a pH-sensitive alginate hydrogel as electrolyte (Figure 17a,b), which is biocompatible and biodegradable. To demonstrate the efficiency of such hydrogels to host bioreceptor without damaging its bioactivity, glucose oxidase was entrapped into the alginate in order to make a biosensor.…”
Section: Other Type Of Electrolytementioning
confidence: 99%
“…Representative image of alginate gelation process by continued calcium cations. Reprinted from Dumitru et al [39], an open access article distributed under the terms of the creative commons by attribution 4.0 (CC-BY 4.0).…”
Section: Figurementioning
confidence: 99%